Development of the Cryptocurrency Addiction Scale: A Methodological Study - Suleyman Umit Senocak; Tarik Totan and Fatma Demirkiran (Professor Despina Sapountzi-Krepia, 2024)
Development of the Cryptocurrency Addiction Scale: A Methodological Study